A debate on mathematical modeling in the curriculum of basic education mathematics teacher training courses in the city of Humaitá – Amazonas (Research, Society and Development, 2022)
The present work discusses the importance of mathematical modeling as a method of teaching and learning mathematics in basic education, capable of favoring significant experiences in the school context, with emphasis on the curriculum of basic education mathematics teacher training courses. Its general objective was to describe training courses for mathematics teachers from the main higher education in the Municipality of Humaitá, State of Amazonas, which include this teaching practice in their curricula. This city in Amazonas was chosen considering its importance as a university center in the interior of Amazonas, which requires institutions such as the Institute of Education, Agriculture and Environment Amazonas. A bibliographic review research was carried out, with the analysis of articles, books, dissertations and theses related to the subject in question, which provided theoretical support for the writing. On the Other hand, information was collected on the presence of mathematical modeling as subject in the curriculum of such higher education institutions, the target of this research, which helped to highlight the importance of teaching and learning practices aligned with the methodology of mathematical modeling, even if its non-consolidation in the curricula of initial teacher training courses is notorious.